Fundamental aerodynamics of a new volleyball - Asai, T.; Ito, S.; Seo, K.; Hitotsubashi, A. (Sports Technology, 2010)
This study compared the basic aerodynamic characteristics of conventional volleyballs with those of new designs in a wind tunnel. Furthermore, to examine the aerodynamic instability near the critical Reynolds regime (14 m/s), balls were propelled with an impact-type ball ejection device and the variation in the coordinates of the landing point was measured. It was found that the critical Reynolds number for a conventional volleyball (Molten MTV5SLIT) was approximately 2.7 x 10^5, whereas that for a design with honeycomb surface protrusions (Molten V5M5000) was slightly lower at approximately 2.2 x 10^5. The honeycomb-type balls showed a drag coefficient of approximately 0.17 when supercritical, which is rather large compared with that of conventional balls (0.1). It is believed that the honeycomb surface protrusions increase the roughness of the ball surface, and this presumed increase in roughness implies a trend towards reduced aerodynamic instability close to critical Reynolds numbers.